Eufemisme dalam Bahasa Sasak Dialek Ngeto Ngete: Kajian Makna dan Faktor Penyebab - Nuri Nazir, Yuniar; Mari (Humanis, 2025)
The objectives of this study are divided into two, namely specific objectives and general objectives. The specific objective is to describe the factors causing euphemism. Data were collected using the listening method, the speaking method, and the elicitation method. The listening method is assisted by basic techniques, namely the tapping technique and advanced techniques, namely the listening technique involving speaking, the listening technique free involving speaking, the recording technique, and the note-taking technique. The speaking method is assisted by basic techniques, namely the fishing technique and advanced techniques, namely the speaking technique. Data analysis was carried out using the comparative synchronic descriptive method assisted by the substitution technique. The results of the data analysis are presented using the informal method and with inductive and deductive techniques. This study was conducted in the village of Dasan Boroq, East Lombok. The number of native speakers of the Ngeto Ngete dialect Sasak language in this village is 1,600. For the research sample, 16 informants were taken randomly horizontally or ordinally. There are four factors that cause euphemisms, namely (1) the trust factor, (2) the comfort factor, (3) the politeness factor, and (4) the honor factor.